Clinical and Laboratory Evaluation of Cases with Familial Hypercholesterolemia: A Multicentre Study - Akgün, Abdurrahman; Uzunyayla, Gozde; Gücüyener, Neslihan; Zubarioglu, Tanyel; Ister, Meral Bahar; Unal, Ozlem; Zeybek, Ayse Cigdem Aktuglu (My University, 2025)
Aim: Familial hypercholesterolemia leads to the buildup of atherosclerotic plaques in the arteries, greatly elevating the risk of early- onset coronary heart disease. The objective of this study was to examine the clinical, laboratory, and genetic profiles of patients affected by familial hypercholesterolemia. Methods: A retrospective review was performed on the demographic, clinical, biochemical and genotypic profiles of 124 individuals diagnosed with familial hypercholesterolemia. Results: These cases from 6 centres comprised 50.8% males and 49.2% females. There was a history of hypercholesterolemia in the mothers of 43.5% of the cases and in the fathers of 53.2%. At the time of diagnosis, 81.5% of the cases had no complaints, 3.2% had skin lesions and 3.2% had weight gain complaints. Mutations were detected in the LDLR gene in 95.2% of the cases, in the APOE gene in 3.2% and in the APOB gene in 1.6%. Conclusion: Familial hypercholesterolemia cases are still under-detected both in Türkiye and worldwide. Consequently, the prevention of coronary artery diseases caused by hypercholesterolemia is not feasible, underscoring the need for implementing more robust and widespread screening protocols.
Keywords: Atherosclerosis; LDL-cholesterol; Familial hypercholesterolemia; Lipoprotein apheresis